(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The influence of inclined magnetic field, Hall currents, chemical reaction and dissipation on non-Darcy convective heat and mass transfer flow of nanofluid through a porous medium past a exponentially stretching sheet with space temperature dependent in sources is considered employing Runge-Kutta –Shooting method the equations have been evaluated for different variations. It is observed that an increment in the inclination  reduces the linear velocity, nanoparticle volume fraction and enhances the rotational velocity ,temperature an increment in the inclination of the magnetic field reduces the linear velocity, nanoparticle volume fraction and enhances the rotational velocity, temperature